RISK MANAGEMENT STRATEGY: ANALYSIS OF THE EFFECTS OF MOTIVATION, INCENTIVES, AND CAREER DEVELOPMENT ON ORGANIZATIONAL PERSONNEL - Lubis, Nurul Rafiqoh; Mutthaqin, Muhammad Satrya; sugianto, Sugianto (Proceeding International Seminar of Islamic Studies, 2024)
This research delves into the impact of motivation, incentives, and career development on the workforce at PT. Telkomsel Grapari Medan. The study was conducted in response to employee dissatisfaction with PT. Telkomsel's management regarding the non-payment of allowances, leading to large-scale demonstrations. Field data collection was carried out through questionnaires, and data analysis used the multiple analysis method. This analytical technique was employed to assess the influence of independent variables on the dependent variable. The analysis process was conducted with the assistance of SPSS 26.0 for Windows software. The research findings indicate that motivation and career development simultaneously have a significant impact on the workforce at PT. Telkomsel Grapari Medan. This conclusion is based on the F-value of 18.533 with a significance level of 0.000. Partially, both motivation and career development have a significant impact on the workforce. This is evident from the T-values of motivation at 4.539 and career development at 2.891, exceeding the T-table value of 1.996. Meanwhile, the incentive variable does not have a partial impact on the workforce because its T-value is smaller than the T-table value.